2021
DOI: 10.1002/psc.3327
|View full text |Cite
|
Sign up to set email alerts
|

Membrane fusion mediated by peptidic SNARE protein analogues: Evaluation of FRET‐based bulk leaflet mixing assays

Abstract: Peptide‐mediated membrane fusion is frequently studied with in vitro bulk leaflet mixing assays based on Förster resonance energy transfer (FRET). In these, customized liposomes with fusogenic peptides are equipped with lipids which are labeled with fluorophores that form a FRET pair. Since FRET is dependent on distance and membrane fusion comes along with lipid mixing, the assays allow for conclusions on the membrane fusion process. The experimental outcome of these assays, however, greatly depends on the app… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 32 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…In other words, when the emission spectrum of one fluorescent molecule overlaps with the absorption spectrum of another fluorophore and the distance between the two fluorophores is appropriate, the phenomenon of FRET from the donor to the receptor can be observed. Thus far, considerable progress has been made in simulating natural light harvesting by transferring energy from a donor to a receptor through FRET [12–15] . For example, Guo et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In other words, when the emission spectrum of one fluorescent molecule overlaps with the absorption spectrum of another fluorophore and the distance between the two fluorophores is appropriate, the phenomenon of FRET from the donor to the receptor can be observed. Thus far, considerable progress has been made in simulating natural light harvesting by transferring energy from a donor to a receptor through FRET [12–15] . For example, Guo et al.…”
Section: Introductionmentioning
confidence: 99%
“…Thus far, considerable progress has been made in simulating natural light harvesting by transferring energy from a donor to a receptor through FRET. [12][13][14][15] For example, Guo et al reported WP6-G-NiR and WP6-G-ESY systems, which exhibited high antenna effects (AEs). [16] Notably, most studies on ALHSs have employed organic solutions; however, owing to the stability of polymer gels, ALHSs show greater promise in polymer gel materials.…”
Section: Introductionmentioning
confidence: 99%